Emerging Trends in Pharmacological Strategies for Targeting Neuroinflammation in Depression - Kumari, Anshu; Sharma, Rahul Kumar; Chopra, Shivani; Chopra, Hitesh (Scripta Medica, 2025)
The article discusses evolving pharmacological strategies for addressing the neuroinflammation in depression, highlighting its role in major depressive disorder. Neuroinflammation is linked to neurotransmitter imbalances, hypothalamic-pituitary- adrenal axis dysregulation and impaired neurogenesis. Key treatments explored include anti-inflammatory agents such as N-acetylcysteine, toll-like receptor (TLR) inhibitors and cytokine blockers like anti-interleukin-6 and tumour necrosis factor alpha (TNF-α) agents. Glutamate modulation, antioxidants and omega-3 fatty acids are also examined for their therapeutic efficacy. The article emphasises the need for combination therapies and novel approaches like ketamine and microbiome-targeted treatments to combat inflammation-related depression. Despite significant progress, further research is needed to fully understand the mechanisms and optimise therapeutic strategies.